(untitled) (Journal of Partial Differential Equations, 2018)
In the paper, we consider the existence and uniqueness results for Caputo fractional differential equations with integral boundary value condition. The sufficient conditions of existence and uniqueness are obtained by applying the contraction mapping principle, Krasnoselskii’s fixed point theorem and Leray-Schauder degree theory, which partly improves and extends the associated results of fractional differential equations. Four examples illustrating our main results are included.